Active research and quality of the diagnosis of occupational disease: the experience of the Occupational Medicine Division of ASST Papa Giovanni XXIII in Bergamo - Mosconi, Giovanni; De Ponti, Simona; Santini, Marisa; Riva, Matteo Marco; Leghissa, Paolo; Cannistraro, Valeria; Borleri, Daniela (La Medicina del Lavoro, 2018)
Authors describe initiatives of active research promoted by the Occupational Medicine Division of ASST Papa Giovanni XXIII in Bergamo. The initiatives aimed at improving the quality of diagnosis of occupational disease and their emersion in the province. They have been carried out in collaboration with social partner organizations, joint consultation, occupational physician, general practitioners and specialists in other medical disciplines. Initiatives described in this paper have led to increased reports of occupational disease, to improve the quality of diagnosis (excellent ratio between diagnosis and recognition from INAIL), to document new cases of work-related diseases and the occupational risk factors that have determined them. Results obtained highlight the importance, also for diagnosis of work-related diseases, of an effective collaboration between all actors of prevention, both internal and external to the company. Collaboration is specially useful for small and medium-sized companies, the least equipped to deal with prevention activities, given the modest economic and organizational commitment necessary for their implementation.